Pengelolaan Supervisi Artistik Kepala Sekolah Dasar Negeri 1 Selojari Klambu Grobogan - Siti Musrikah (Jurnal VARIDIKA, 2016)
This study aimed to describe and analyze the implementation of the artistic supervision of Selojari 1 elementary school and to describe and analyze any obstacles faced in learning supervision artistict. Type of this research research is called qualitative research. The collection of data carried out by means of in depth interviews, observations, and use of documents. Data were analyzed with data reduction, data presentation, and draw conclusions. The result of this research showed that artistic supervision planning in Selojari 1 elementary school is to make an systematic artistic supervision format. Implementation of artistic supervision through classroom visits, observe teaching learning activities and also classroom administration aspec. Supervision carried out periodically. Implementation feedback artistic supervision carried out by the headmaster as supervisor by making a connection humanist, harmonious and appreciate the personal character and talents of teachers.